Strategy for starting a business in the new normal phase of pandemic Covid19 in some types of SME in Padang City / Toti Srimulyati, John Edwar and Mulyadi - Srimulyati, Toti; Edwar, John, Mulyadi (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The world changed at the end of 2019 with the COVID 19 pandemic (Corona Virus Disease 19). The impact of the Covid19 pandemic is very different from the economic crisis, where Small and Medium Enterprises (SMEs) were businesses that could still survive. In this covid19 pandemic situation, SMEs cannot survive and even have to be closed. The problem of this research is "what strategies can be done by MSMEs to start a business in the new normal Covid19 phase as seen from the types of SMEs in the city of Padang". It is hoped that the results of this research can provide information to the Regional Government of Padang City and parties who need to see the conditions and facts that have occurred in Padang City SMEs during the new normal pandemic COVID 19. The object of the research is the SMEs in the city of Padang which includes 14 types of SMEs. Sampling is done on-line, the research variables that will be used are in the form of sales or revenue turnover, labour and suppliers that support SME activities. Data analysis was carried out qualitatively. In this new normal phase, SME entrepreneurs try to start a business again, especially for businesses that were completely closed during the PSBB (Large-Scale Social Restriction) phase. The business strategy carried out by this MSME entrepreneur is to prepare a little food first and also serve on-line purchases and payment done is Cash on Delivery (COD). For non-food businesses, they still open their shops but with fewer employees. There are still many businesses that were opened during the initial period of the COVID-19 pandemic. The business strategy undertaken to be able to survive during the PSBB phase for SMEs that remain open is to serve online sales and consumers can order goods from home and entrepreneurs deliver directly to their address. In general, payments are made on the spot when the goods are delivered, especially for foodstuffs.